Eficácia de um novo tipo de capacete para oferta de CPAP, o elmo, no tratamento da insuficiência respiratória aguda hipoxêmica secundária à Covid-19 - Tomaz, Betina Santos (2021)
Approximately 15 to 20% of COVID-19 cases develop acute hypoxemic respiratory failure (AHRF) requiring oxygen therapy and ventilatory support. Noninvasive strategies to avoid intubation in these patients have become increasingly important. Continuous Positive Airway Pressure (CPAP) with a helmet interface has been described as a safe strategy, with minimal contamination of the environment, improving patient oxygenation and avoiding intubation in more than half of the cases. The aim of this study was to assess the efficacy of using a new type of helmet, the ELMO, to treat acute hypoxemic respiratory failure secondary to COVID 19 outside the ICU. It was a proof-of-concept study performed on adult patients with moderate to severe AHRF secondary to COVID-19, admitted to the wards of a public hospital. The intervention consisted in applying the ELMO interface which consists of a helmet integrated to oxygen and compressed air flow meters of 30L/min each and a PEEP valve capable of offering CPAP levels of 8 to 15 cmH2O. Data were recorded before and after 1 hour while using the device while the patient was monitored for cardiorespiratory parameters, adverse events and comfort. Successful treatments with ELMOcpap were considered to be cases in which there was a reduction in the need for oxygen therapy, characterized by the use of a low-flow oxygen nasal catheter <3L/min or total withdrawal of oxygen support and no need for orotracheal intubation. Ten patients completed the protocol. The ELMOcpap was well tolerated with no relevant adverse effects observed, and its use was feasible outside the ICU for a prolonged and successful time in 60% of the patients. A CPAP of 10cmH2O with a total gas flow of 56 to 60L/min improved oxygenation after 1 hour of use, allowing a reduction in the estimated FIO2 (p = 0,014) raising the estimated PaO2/ FIO2 from 88 [80,5-126] to 212 [131-290,5] (p = 0,008) in the first hour without causing CO2 rebreathing or hypercapnia. In conclusion, the use of the helmet device ELMO is feasible and effective in delivering high-flow CPAP to patients with AHRF caused by COVID-19 outside the ICU without major adverse effects and with good comfort. Its application significantly improved oxygenation which contributed to reduce FIO2 without CO2 rebreathing. The overall success rate was 60% in this pilot study. The data from the present work support future clinical trials with this new interface.